2002
DOI: 10.1016/s0896-6273(02)00683-9
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Function of a Glial Subtype in the Vertebrate Peripheral Nervous System

Abstract: Glia-axon interactions are essential for the development and function of the nervous system. We combine in vivo imaging and genetics to address the mechanism by which the migration of these cells is coordinated during embryonic development. Using stable transgenic lines, we have followed the migration of one subset of glial cells and their target axons in living zebrafish embryos. These cells coalesce at an early stage and remain coupled throughout migration, with axons apparently pathfinding for glia. Mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
229
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(240 citation statements)
references
References 32 publications
10
229
0
Order By: Relevance
“…Labeling of the migrating AN glial cell population with anti-glutamine synthetase antibody shows that glial cells often appear in chains, as has been seen in other systems (Sepp et al, 2000;Gilmour et al, 2002;Silies et al, 2007;von Hilchen et al, 2008, Aigouy et al, 2008 (Fig. 3 A-D).…”
Section: Development Of the Glial Network In The Antennal Nervesupporting
confidence: 72%
“…Labeling of the migrating AN glial cell population with anti-glutamine synthetase antibody shows that glial cells often appear in chains, as has been seen in other systems (Sepp et al, 2000;Gilmour et al, 2002;Silies et al, 2007;von Hilchen et al, 2008, Aigouy et al, 2008 (Fig. 3 A-D).…”
Section: Development Of the Glial Network In The Antennal Nervesupporting
confidence: 72%
“…NRG1 signaling is also important in directed cell migration of SCPs as shown by elegant studies in the zebrafish by Gilmour et al (2002), and subsequently by Lyons et al (2005) (reviewed in Lai, 2005). By analyzing different zebrafish mutants, these researchers showed that axons provide guidance cues, in the form of ErbB signaling, for directed migration of SCPs.…”
Section: Axonal-glial Interactions In Developing Nerves and Their Impmentioning
confidence: 99%
“…Interneuromast cells deposited by primI are normally kept quiescent for several days by the glial cells that accompany the afferent axons (Grant et al, 2005;Lopez-Schier and Hudspeth, 2005). Ganglion ablation prevents the migration of glial cells along afferent axons (Gilmour et al, 2002), therefore leading to precocious proliferation of interneuromast cells and to the formation of intercalary neuromasts. We examined the extent of reinnervation after ganglion ablation at 24 hpf in seven SqET20 embryos, where the mantle cells of neuromasts and the interneuromast cells express GFP (Parinov et al, 2004).…”
Section: Neuromast Innervation By the Regenerated Ganglionmentioning
confidence: 99%